pemerolehan bahasa anak usia 2,5 tahun dalam aspek fonologi - yogaputra Nur Pratama; ika mustika; aurelia saktiyani (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2020)
Researchers assess children's language acquisition occurs in the environment where the child lives. A child who grows up in a talkative family will influence the child's speech development. In this case, the aim of the research was to find out how to pronounce children aged 2.5 years from the phonological aspect. This research was conducted for 7 days using descriptive qualitative methods. The data obtained were obtained from direct observation, daily notes, and interviews with the mother. The data obtained came from F, the second son of the pair N and B. The findings in this study were that F was able to pronounce vowels clearly. Meanwhile, the consonant letter F still has difficulty pronouncing it and replacing it with another letter. For example, F still pronounces the letter [S] with 'tc'. This happens because the tool for saying F is not yet mature and is not yet familiar with the letter in question.